Investigating the molecular mechanisms of Fuzheng Yiliu Shenji prescription in SH-SY5Y neuroblastoma cells - Zhu, Xueying; Si, Yinchu; Gai, Cong (Frontiers in Oncology, 2024)
BackgroundNeuroblastoma is the most common extracranial solid tumor in childhood. Fuzheng Yiliu Shenji Prescription (FYSP) has shown potential in treating malignant pediatric tumors in clinical settings. This study aims to explore the molecular mechanisms behind its effects, specifically in the context of neuroblastoma cell lines.ObjectiveTo elucidate the active compounds in FYSP and their mechanisms of action in inhibiting neuroblastoma cell viability, inducing apoptosis, and affecting the cell cycle in SH-SY5Y cells through network pharmacology and empirical validation.Materials and methodsWe identified the major compounds in FYSP and their predicted targets, constructing a protein-protein interaction (PPI) network and performing GO and KEGG pathway analyses. The effects of FYSP were empirically validated through assays on cell viability, cell cycle, apoptosis, and protein expression in SH-SY5Y cells.ResultsThe study identified 172 active chemical components in FYSP, with 188 common targets related to neuroblastoma. Network analysis highlighted the PI3K-Akt pathway as a significant target. Experimental validation in SH-SY5Y cells confirmed that FYSP could inhibit cell viability, induce G2/M cell cycle arrest, and promote apoptosis through modulation of the PI3K-Akt pathway, specifically upregulating caspase-3 and downregulating Bcl-2/Bax expression.ConclusionThe study elucidates the molecular basis of FYSP’s effects on neuroblastoma cells in vitro, demonstrating its ability to modulate key pathways involved in cell cycle and apoptosis. While these findings suggest a potential therapeutic role for FYSP, they are limited to in vitro observations, and further research, including in vivo studies, is necessary to explore its clinical applicability.